2011
DOI: 10.1111/j.1741-2358.2009.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliative cytology of the oral mucosa in burning mouth syndrome: a cytomorphological and cytomorphometric analysis

Abstract: doi:10.1111/j.1741‐2358.2009.00319.x 
 Exfoliative cytology of the oral mucosa in burning mouth syndrome: a cytomorphological and cytomorphometric analysis Objective:  The aim of this study was to evaluate oral epithelial cells by exfoliative cytology in burning mouth syndrome (BMS). Material and methods:  Oral smears were collected from clinically normal‐appearing mucosa by liquid‐based exfoliative cytology in 40 individuals (20 BMS patients and 20 healthy controls matched for age and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Atrophy of the oral mucosa due to vitamin B12 deficiency or the xerostomia of aging are known to be causes of secondary BMS. A recent cytomorphologic study provides evidence that mucosal atrophy may be a factor in primary BMS (35). Buccal musosal exfoliative cytology identified a high nuclear to cytoplasmic ratio and an increased number of nucleated cells in patients with BMS versus age‐ and sex‐matched controls.…”
Section: Etiologymentioning
confidence: 99%
“…Atrophy of the oral mucosa due to vitamin B12 deficiency or the xerostomia of aging are known to be causes of secondary BMS. A recent cytomorphologic study provides evidence that mucosal atrophy may be a factor in primary BMS (35). Buccal musosal exfoliative cytology identified a high nuclear to cytoplasmic ratio and an increased number of nucleated cells in patients with BMS versus age‐ and sex‐matched controls.…”
Section: Etiologymentioning
confidence: 99%
“…Epithelial atrophy has also been described in a study that concluded that it could lead to greater exposure of nervous terminations and the consequent symptoms described for this syndrome 61 .Low density of intraepithelial nervous fibers was observed on area and length basis in samples of the tongue dorsum mucosa 62 .…”
Section: Histological Changes In the Oral Mucosamentioning
confidence: 89%
“…A previous study on the oral mucosa using exfoliative cytology revealed significant morphometric changes in the oral epithelial cells of BMS patients. These changes appear associated with epithelial atrophy and a dysregulation of the maturation process, which consequently can lead to oral pain (Wandeur et al, ). Along this line, we have recently investigated the epithelial thickness and distribution of oestrogen receptor in lingual biopsies from patients with BMS and healthy women (Jørgensen et al, ).…”
Section: Discussionmentioning
confidence: 99%